PERAN AKTIVITAS PENCIPTAAN PENGETAHUAN SEBAGAI PEMEDIASI PADA PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP INOVASI ORGANISASI - Candra Vionela Merdiana (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
This study has the main purpose to test and explore the role of knowledge creation activities as mediation on the inï¬‚ uence of transformational leadership style to organizations of innovation in the Micro, Small and Medium Enterprises (SME) production sector in Yogyakarta. This research is a quantitative research using a survey method. The sampling technique used is non probability sampling with purposive sampling method. The unit of analysis used in this study is an organization that is represented by the owners or managers of SMEs in the production sector of Yogyakarta. Questionnaires were distributed as many as 40, the questionnaire is not returned and not in accordance with the criteria of as much as 6 SME production sector. So that the number of respondents who used as many as 34 respondents in 34 SMEs production sector. Testing transformational leadership style on organizational innovation mediated by the activity of knowledge creation is done by using multiple linear regression analysis. Due to the use of mediation, the mediation testing using Baron and Kenny (1986). Based on the results of multiple linear regression analysis using Baron and Kenny (1986), then the results are as follows: transformational leadership style positive and signiï¬ cant impact on organizational innovation, knowledge creation activity while not mediate the eï¬€ ect of transformational leadership style to organizational innovation.